ANALISIS PROSEDUR PELAYANAN PENGURUSANSURAT IZIN PRAKTEK DOKTER DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KOTA PEKANBARU - Inda Ayu Nengsih; Herman Herman (UIR Press, 2018)
The purpose of this research is to know the Analysis of Procedure of Medical Doctor Practice Permit Management Service at One Stop Service and One Stop Service (DPMPTSP) City Pekanbaru. Assessment indicators used include service procedures, completion time, service costs, service products, facilities and infrastructure, employee competence. Research method used is quantitative method. This method can be categorized as descriptive research that prioritize the list of kusioner as a means of collecting data and data collected with this tool then used as the main raw material to analyze the empirical condition of the objectivity of the existence of research objectives at the condition of the researcher. The location of this research at the Department of Investment and Integrated Pestanan One Door (DPMPTSP) Pekanbaru. For physician licensed field officers use census techniques and for doctors who administer licensing practice using purposive sampling samples. Based on this analytical technique, the research evaluates and concludes that the Analysis of Procedure of Doctor's Practice Document Management Service at One Stop Service and One Stop Service (DPMPTSP) Pekanbaru in serving the doctor is at good enough assessment interval. Recommendations that need to be considered especially with respect to Analysis of Service Procedures that must be optimized again to improve employee performance and time of completion of the doctor's licensing practice so that doctors - doctors feel satisfied with the performance of employees.